Progress in green hydrogen adoption in the African context - Obanor, Enoch I.; Dirisu, Joseph O.; Kilanko, Oluwaseun O.; Salawu, Enesi Y.; Ajayi, Oluseyi O. (Frontiers in Energy Research, 2024)
Hydrogen is an abundant element and a flexible energy carrier, offering substantial potential as an environmentally friendly energy source to tackle global energy issues. When used as a fuel, hydrogen generates only water vapor upon combustion or in fuel cells, presenting a means to reduce carbon emissions in various sectors, including transportation, industry, and power generation. Nevertheless, conventional hydrogen production methods often depend on fossil fuels, leading to carbon emissions unless integrated with carbon capture and storage solutions. Conversely, green hydrogen is generated through electrolysis powered by renewable energy sources like solar and wind energy. This production method guarantees zero carbon emissions throughout the hydrogen’s lifecycle, positioning it as a critical component of global sustainable energy transitions. In Africa, where there are extensive renewable energy resources such as solar and wind power, green hydrogen is emerging as a viable solution to sustainably address the increasing energy demands. This research explores the influence of policy frameworks, technological innovations, and market forces in promoting green hydrogen adoption across Africa. Despite growing investments and favorable policies, challenges such as high production costs and inadequate infrastructure significantly hinder widespread adoption. To overcome these challenges and speed up the shift towards a sustainable hydrogen economy in Africa, strategic investments and collaborative efforts are essential. By harnessing its renewable energy potential and establishing strong policy frameworks, Africa can not only fulfill its energy requirements but also support global initiatives to mitigate climate change and achieve sustainable development objectives.